2021
DOI: 10.51273/esc21.2517121
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protective Effect of Ajwa Seed And Fruit on Renal Histopathological Changes in Diabetic Nephropathic Rats

Abstract: Objective: To investigate the protective effect of Ajwa date seed and fruit on renal histological changes in alloxan induced diabetic rats. Methods: This was an experimental study and was conducted in Post Graduate Medical Institute. The duration of study was 6 weeks. In this study random allotment of 32 rats was done in four groups. Group 1 was treated as control. Diabetes was induced in the 2nd, 3rd and 4th group by alloxan injection intra peritoneally. Group 2 was diabetic non treated while group 3 and 4 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[21][22] Previous studies confirmed the numerous protective and clinical properties of Ajwa date, including antioxidant, anti-inflammatory, nephroprotective, and hepatoprotective activities. [23][24][25][26] that stem from…”
mentioning
confidence: 99%
“…[21][22] Previous studies confirmed the numerous protective and clinical properties of Ajwa date, including antioxidant, anti-inflammatory, nephroprotective, and hepatoprotective activities. [23][24][25][26] that stem from…”
mentioning
confidence: 99%